New Evidence on the Valuation Effects of Convertible Bond Calls - Datta, Sudip; Iskandar-Datta, Mai (Journal of Financial and Quantitative Analysis, 1996)
This study examines the wealth effects of convertible bond call announcements on stockholders, straight bondholders, and called and non-called convertible debtholders. We document that forced conversions are associated with a significant loss in firm value. The results suggest that convertible call announcements can trigger both negative signal and wealth transfer effects. We show that at least part of the negative effect on stock prices results from wealth transfer to straight bondholders. Our analysis also lends empirical validity to the common contention that called convertible bondholders suffer wealth expropriation due to the elimination of the premium. The wealth effect on non-called convertible debtholders is insignificant. Cross-sectional analysis reveals that the negative signal effect is important in explaining bond, stock, and firm excess returns. Finally, we present evidence that refutes the notion that bonds are called to relieve the firm from restrictive debt covenants.